Comparison of plants used for skin and stomach problems in Trinidad and Tobago with Asian ethnomedicine - Lans, Cheryl (BioMed Central, 2007)
This paper provides a preliminary evaluation of fifty-eight ethnomedicinal plants used in Trinidad and Tobago for skin problems, stomach problems, pain and internal parasites for safety and possible efficacy. Thirty respondents, ten of whom were male were interviewed from September 1996 to September 2000 on medicinal plant use for health problems. The respondents were obtained by snowball sampling, and were found in thirteen different sites, 12 in Trinidad and one in Tobago. The uses are compared to those current in Asia. Bambusa vulgaris, Bidens alba, Jatropha curcas, Neurolaena lobata, Peperomia rotundifolia and Phyllanthus urinaria are possibly efficacous for stomach problems, pain and internal parasites. Further scientific study of these plants is warranted.